172 Comparing Patient Satisfaction in Penile Prosthesis Surgery after Radical Prostatectomy Versus the General Population. (1st May 2022) - Howell, S.; Palasi, S.; Green, T.; Kannady, C.; Slaughter, K.; Wang, R.; Yang, B.
ABSTRACT: Introduction: Penile prosthesis surgery (PPS) is currently a widely used treatment option for ED. Men who receive PPS following radical prostatectomy (RP) are generally satisfied with the outcome. Objective: This study seeks to examine patient satisfaction with PPS and to determine if a difference in satisfaction exists in post-prostatectomy ED patients versus the general population. We hypothesize that the etiology of ED does not affect patient satisfaction following PPS. Methods: 164 patients who received PPS at our institution from August 2017 to December 2019 were given a validated 14 item questionnaire, Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS), to assess their satisfaction with PPS. 102 patients responded at 6 months following surgery and were enrolled in this study. These patients' charts were retrospectively reviewed for demographic information and information regarding the etiology of their ED. Patients were then assigned to one of two groups: patients with post-prostatectomy ED (study) and all other etiologies (control). We found no significant difference in age or race between the two groups. Patients in the study group were further assigned to a subgroup based on the specific procedure they had received: radical prostatectomy (RP) or radical cystoprostatectomy (RCP). Results: Responses to three questions were analyzed: overall satisfaction, whether the procedure met expectations in the past four weeks, and confidence in ability to participate in sexual activity. Chi-square analysis was performed to determine the difference in the distribution of response rates. There was no difference in reported overall satisfaction (p=0.96), expectations (p=0.78), or confidence (p=0.78) between post-prostatectomy patients and all other etiologies of ED. On subgroup analysis, there was no difference in reported overall satisfaction (p=0.47) or confidence (p=0.080) between patients with RP compared to patients with RCP. RP and RCP patients differed in whether the PPS met expectations (p=0.033). 'RP patients reported a mean of 3.5/4 compared to CRP patients who reported an average value of 3.0/4. Conclusions: Our analysis suggests that the distribution of responses to the EDITS questionnaire are not significantly different between patients whose etiology of ED is post-prostatectomy compared to all other etiologies. Overall satisfaction, whether the treatment meets expectations, and confidence in the ability to participate in sexual relations are not significantly different between these patients. Disclosure: Work supported by industry: no.